Implementation of the Project “Community Police Officer”: Real Actions to Bring Police Service Closer to People (on the example of Kharkiv oblast) - M. V. Holub (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied the issue of further approach of the police service to the people – members of the united territorial community. The emphasis has been placed on the need to take further steps to strengthen partnership between the police and community members. Special attention has been paid to the important role of the National Police in the process of implementing the decentralization, taking measures to ensure public order and security in the territories of united communities, taking into account the views, positions and recommendations of residents of united territorial communities, the importance of interaction between community police officers and the population. The author has highlighted the importance of the pilot project “Community Police Officer” to further increase of public confidence in the police. The author has suggested appropriate measures for more effective promotion of this project, in particular: to initiate for the Department of the National Police of Ukraine to take measures aimed at creating a legal base that can ensure the effective operation of community police officers according to the legal point of view, as well as their interaction with other law enforcement agencies, introducing relevant amendments into existing regulatory documents; to prepare propositions in regard to these provisions; to develop routes and time of foot patrol by community police officers of the assigned territory, taking into account the analysis of street offenses, the location of places visited by a significant number of residents of the united territorial communities and other features of a particular united community; to make propositions for the creation of a “basic” united territorial communities in Kharkiv oblast, in terms of community police officers’ activities, to initiate and provide assistance to the Department of Preventive Activities of the Main Directorate of the National Police in Kharkiv oblast in organizing and conducting practical classes with this category of employees with visiting the specified united territorial communities; to introduce training of community police officers on the basis of Kharkiv National University of Internal Affairs, to prepare appropriate educational and methodical material; to improve the work of community police officers to ensure effective exchange of information, opportunities to quickly make decisions in case of complications, create an Internet group in the application “Telegram”, which should include police officers working within the pilot project “Community Police Officer”.